RANCANG BANGUN ALAT KENDALI PID UNTUK MENJAGA KESTABILAN SUHU PEMANAS PADA PROSES DISTILASI PENGHASIL BIOETANOL - , MUHAMMAD NUR FATTAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bioethanol is a renewable energy and fuel replacement for gasoline is highly prospective. In manufacturing, there are several stages of the process, one of which is distilled process. Distillation (refinering) is the process of heating raw materials which require a stable temperature to separate the substances in accordance with the type of raw materials used. The raw material used is fermented bananas containing 5% alcohol with purity. The prototype tool is designed automatic temperature control system using industry standards such as the electronic control of the SCR (Silicone Controlled Rectifier) with a closed system of controlling method and the temperature sensor Thermocouple Type-K. With the aim to not only provide a process setpoint value, but also to get feedback so as to control the temperature of the system and applying some of the best industry standard components in this prototype. Test results distillation heating control with PID control parameters are obtained using the Ziegler-Nichols method. This prototype is able to maintain a stable temperature in the distillation process is maintained at a temperature setpoint of 75 Â° C to produce bioethanol with a purity of 97%.